2000
DOI: 10.1002/1528-252x(200010)17:7<217::aid-pdi45>3.3.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Improving the outcome for children and adolescents with type 1 diabetes: results of a changing service in Copenhagen

Abstract: In 1995, an international study of HbA 1c levels in 22 centres showed that our centre in Glostrup, Copenhagen, recorded a mean HbA 1c signi®cantly above the average. As a consequence, we instituted a series of changes in the structure and process of our service. During the period from 1995 to 1998 we have closely monitored and evaluated the human and ®nancial resources to optimise outpatient care. We reorganised the work of the medical and paramedical staff to concentrate more on outpatient than on inpatient m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…A recent study has demonstrated changes in structure and process at a diabetes centre to be followed by improvement in outcome. These changes included reorganizing the work of the health professionals in the diabetes team and the definition of clear standards of care [32].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has demonstrated changes in structure and process at a diabetes centre to be followed by improvement in outcome. These changes included reorganizing the work of the health professionals in the diabetes team and the definition of clear standards of care [32].…”
Section: Discussionmentioning
confidence: 99%
“…However, the range of changes made suggests that the two centers may have undergone a more fundamental restructuring of care rather than just tinkering with service provision. Increased numbers of diabetes nurses, weekly staff meetings, written patient information, and increased visits may have lead to improved education and/or treatment adherence (17). In comparison, the DCCT/ Epidemiology of Diabetes Interventions and Complications results in adolescents show that in both DCCT intensive and nonintensive groups the mean A1C levels of ϳ8.4% suggest that this age-group requires a fundamentally different approach to obtain a significant improvement in metabolic outcome (18).…”
Section: Assessment Of Stability Of Center Differencesmentioning
confidence: 99%
“…Previous studies show that many children and adolescents do not achieve satisfactory blood glucose control [1–4]. Improved blood glucose regulation is associated with a significantly lower risk of developing complications such as nephropathy, retinopathy, and neuropathy [5–7].…”
Section: Introductionmentioning
confidence: 99%